Determination of the yield, enzymatic and metabolic response of two Capsicum spp. cultivars to deficit irrigation and fertilization using the stable isotope 15N - Tilen Zamljen; Sonja Lojen; Vesna Zupanc; Ana Slatnar (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Background Climate change is increasingly impacting agriculture all over the world, with extended periods of drought, flooding, hail, winds and temperature extremes. To negate the effects of climate change, researchers are trying to find new agricultural production techniques, to save resources without losing yield quality and quantity. A study on Capsicum annuum L. 'Chili-AS Rot' and Capsicum chinense Jacq. 'Naga Morich' chilies, grown under field capacity, deficit irrigation (50% field capacity) and full and half dose of mineral fertilizer in peat soil substrate was conducted. Both cultivars were marked with the stable isotope 15N, to follow nitrogen translocation in chili plants under stress conditions. Results The yield and plant biomass, capsaicin synthase (CS), phenylalanine ammonia lyase (PAL), and peroxidase (POX), as well as total and individual capsaicinoids were studied. In 'Chili-AS Rot' the deficit irrigation with the full-fertilization (Diff) dose showed the highest yield and fruit number, compared to other treatments. In the 'Naga Morich' cultivar the deficit irrigation and half-fertilization (Dihf), showed the highest yield, fruit number and dry weight of chilies, compared to other treatments. In the cultivar 'Chili-AS Rot', deficit irrigation was found to reduce the utilization of N fertilizer when the plant (leaves, stems, and roots) and fruit were considered. The utilization of nitrogen fertilizer was 60 to 70% under deficit fertilization, regardless of the irrigation treatment. The half dose fertilized plants of 'Chili-AS Rot' had higher CS activity and PAL activity (from 50 to 80%) than fully fertilized plants, with deficit irrigation having about 10% higher enzymatic activity than field-capacity irrigated plants. In 'Naga Morich', irrigation treatment affected lower enzymatic activity than field-capacity irrigated plants. Conclusions The results indicate that deficit irrigation and fertilization can be used to maintain enzymatic activity and thus capsaicinoid content, which could reduce the economic cost of irrigation water and fertilizer. It was confirmed that the yield was better under deficit irrigation and fertilization for the more pungent 'Naga Morich'. The result of the study shows that when water and fertilizer use is reduced by up to 50%, chili yield losses are minimal or non-existent. Graphical Abstract